Integrating Traditional Performing Arts and Translanguaging Pedagogy: A Sociocultural Approach to Teaching English through Randai in Indonesia - Miftahurrahmi, Miftahurrahmi; Nurhabibah, Siti (Jurusan Pendidikan Bahasa dan Seni FKIP Universitas Pattimura, 2022)
This study investigates the integration of Randai, a traditional Minangkabau performing art, into English as a Foreign Language (EFL) instruction through a translanguaging pedagogy framed within a sociocultural perspective. The research aims to (1) describe the pedagogical strategies employed by lecturers, (2) analyze translanguaging practices in bilingual (Minangkabau–English) performances, (3) examine students’ perceptions of learning English through local performing arts, and (4) identify contextual enablers and constraints. Using a qualitative ethnographic case study in the English Education Department of Universitas Negeri Padang, data were collected through participant observation, in-depth interviews with lecturers and students, performance and video analysis, and document review of course syllabi and bilingual Randai scripts. Thematic analysis examined pedagogical strategies and perceptions, while discourse analysis explored translanguaging patterns. Findings reveal that Randai was creatively integrated as a medium for performance-based learning, particularly in speaking, storytelling, and intercultural communication. Translanguaging emerged as both a natural and strategic practice that enhanced dramatic expression, conveyed cultural meanings, and facilitated bilingual negotiation. This approach increased student engagement, boosted speaking confidence, and strengthened cultural identity. However, challenges included limited curricular guidelines, rehearsal time constraints, and conservative attitudes toward unconventional pedagogy. The study’s novelty lies in demonstrating how traditional performing arts combined with translanguaging pedagogy create a unique sociocultural model of language learning where linguistic, cultural, and artistic dimensions intersect. The research contributes to educational and linguistic scholarship by broadening translanguaging studies into performing arts and advocating culturally responsive, arts-based EFL pedagogy in Indonesian higher education.